Strategic KAIZEN"! : Using Flow, Synchronization, and Leveling [FSL"! Assessment to Measure and Strengthen Operational Performance - Imai, Masaaki (McGraw-Hill, 2021)
Transform your company's critical operations-and its destiny-through a powerful kaizen-focused strategy designed for 21st century efficiency A pioneer of the operational excellence movement that continues to transform businesses across the world, Masaaki Imai takes you to the next step of continuous improvement-developing an overall strategy for measuring your company's operational performance and improving processes in ways that boost efficiency and gain competitiveness. In Strategic KAIZEN"!, Imai walks you through the process of shifting your focus from volume and speed to his revolutionary Flow, Synchronization, and Leveling (FSL"! evaluation-the most effective Lean paradigm available. At the heart of his approach is the concept of flow-ensuring that each work piece flows between processes without interruption and stagnation. This game-changing guide teaches you: The critical importance of assessing corporate performance from both the financial and operational standpoints How to identify basic structures of the ideal production and operating systems Proven ways of implementing FSL to establish where improvements are most needed and build a strategy that takes you to new heights of corporate performance Certain to be another instant classic from Masaaki Imai, Strategic KAIZEN"!provides an abundance of case studies from companies that have successfully implemented FSL"!and tangible know-how to improve FSL"!status to achieve a lean summit. Whether you run a business, serve in public service, or practice Lean, this groundbreaking guide provides everything you need to transform your organization-and help lead it to the top of your industry, trade, or business